Testing Factor Structure and Measurement Invariance Across Gender With Italian Geriatric Anxiety Scale - Picconi, Laura; Balsamo, Michela; Palumbo, Rocco; Fairfield, Beth (Frontiers in Psychology, 2018)
Late-life anxiety is an increasingly relevant psychiatric condition that often goes unnoticed and/or untreated compared to anxiety in younger populations. Consequently, assessing the presence and severity of clinical anxiety in older adults an important challenge for researchers and clinicians alike. The Geriatric Anxiety Scale is a 30-item geriatric-specific measure of anxiety severity, grouped in three subscales (Somatic, Affective, and Cognitive), with solid evidence for the reliability and validity of its scores in clinical and community samples. Translated into several languages, it has been proven to have strong psychometric properties. In Italy only one recent preliminarily investigative study has appeared on its psychometric properties. However, sample data was largely collected from one specific Italian region (Lombardy) alone. Here, our aim in testing the items of the GAS in a sample of 346 healthy subjects (50% females; 52% from Southern Italy), with mean age of 71.74 years, was two-fold. First, we aimed to determine factor structure in a wider sample of Italian participants. Confirmatory factor analysis showed that the GAS fits an originally postulated three-factor structure reasonably well. Second, results support gender invariance, entirely supported at the factorial structure, and at the intercept level. Latent means can be meaningfully compared across gender groups. Whereas the means of F1 (Somatic) and F3 (Affective) for males were significantly different from those for females, the means for F2 (Cognitive) were not. More specifically, in light of the negative signs associated with these statistically significant values, the finding showed that F1 and F3 for males appeared to be less positive on average than females. Overall, the GAS displayed acceptable convergent validity with matching subscales highly correlated, and satisfactory internal discriminant validity with lower correlations between non-matching subscales. Implications for clinical practice and research are discussed.